2017
DOI: 10.1016/j.ebiom.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Protease Cleavage of Von Willebrand Factor in Glomeruli – An Anti-thrombotic Mechanism in the Kidney

Abstract: Adequate cleavage of von Willebrand factor (VWF) prevents formation of thrombi. ADAMTS13 is the main VWF-cleaving protease and its deficiency results in development of thrombotic microangiopathy. Besides ADAMTS13 other proteases may also possess VWF-cleaving activity, but their physiological importance in preventing thrombus formation is unknown. This study investigated if, and which, proteases could cleave VWF in the glomerulus. The content of the glomerular basement membrane (GBM) was studied as a reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…25 Leukocyte-derived enzymes within the subendothelial glomerular space may help to maintain the balance of pro-thrombotic and anti-thrombotic forces within the kidney. 31 However, to our knowledge, data generated from this SCD cohort are the first demonstrations of ADAMTS13-independent cleavage contributing presented here should therefore be interpreted within the context of this population and we are currently looking to replicate these findings within independent SCD cohorts. Nonetheless, given that leukocyte and endothelial activation appear to be fundamental components of SCD pathophysiology, we anticipate that these findings could be more applicable to the general SCD population.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…25 Leukocyte-derived enzymes within the subendothelial glomerular space may help to maintain the balance of pro-thrombotic and anti-thrombotic forces within the kidney. 31 However, to our knowledge, data generated from this SCD cohort are the first demonstrations of ADAMTS13-independent cleavage contributing presented here should therefore be interpreted within the context of this population and we are currently looking to replicate these findings within independent SCD cohorts. Nonetheless, given that leukocyte and endothelial activation appear to be fundamental components of SCD pathophysiology, we anticipate that these findings could be more applicable to the general SCD population.…”
Section: Discussionmentioning
confidence: 73%
“…Neutrophil proteases have shown capacity to cleave VWF in vitro 25 . Leukocyte‐derived enzymes within the subendothelial glomerular space may help to maintain the balance of pro‐thrombotic and anti‐thrombotic forces within the kidney 31 . However, to our knowledge, data generated from this SCD cohort are the first demonstrations of ADAMTS13‐independent cleavage contributing to VWF regulation in a specific patient population.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…PR3/PRTN3 can also proteolytically activate TNF-α and extracellular IL-1β [43,44]. It has been suggested that PR3/PRTN3 activity may play a protective role in the glomerular basement membrane by cleavage of von Willebrand factor helping to prevent thrombus formation [45]. There is also some evidence to suggest that PR3/PRTN3 activity may contribute to the pathology of other disease states [41,46].…”
Section: Discussionmentioning
confidence: 99%